A War on Terror - Ja’far Muhibullah (International Institute of Islamic Thought, 2005)
If you have never read a Paul Rogers’ article or book before, you will probably be wondering who he is and from what angle he is approaching the “war on terror.” Paul Rogers is a professor of peace studies, as well as an international security correspondent who focuses upon trends in international conflict. More specifically, he examines western military responses to regional conflicts and political violence. It is with this intellectual background that he intends to analyze and understand what is happening in the Middle East (as events occur vis-à-vis “real time”) and predict future implications of Bush’s “war on terror” (p. 2). This book is a compilation of articles that Rogers wrote from October 2001 to December 2002 as weekly columns for the Open Democracy web journal (www.openDemocracy.net). His choice to submit these articles to the web journal, which is neither media-controlled nor affiliated with any special interest group, is a provocative statement that clarifies his position on the media’s “war on terror.” That is, in the author’s words, “media manipulation is easy” (p. 10) and comes “with little or no critical analysis” (p. 15). After editing and refining his articles to prepare them for book form, Rogers divides the articles into seven chapters: Chapter 1: “War in Afghanistan – I,” Chapter 2: “War in Afghanistan – II,” Chapter 3: “A New American Century?,” Chapter 4: “Consequences of War,” Chapter 5: “Israel and Palestine,” Chapter 6: “Winning or Losing?,” and Chapter 7: “Endless War.” He opens the book with a very brief “Introduction” and ends it with a slightly longer “Afterword.” With a closer look, it becomes evident from the chapter titles that underneath the motif of conflict several interrelated issues are presented throughout this book: the Bush administration’s (strike first) political ...